2021
DOI: 10.4269/ajtmh.21-0336
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Knowledge, Attitude, and Practices of Physicians toward Pharmacovigilance at Tertiary Care Hospitals in Khyber-Pakhtunkhwa Province, Pakistan

Abstract: Drug safety assures the effectiveness, safety, and security of drugs, vaccines, and other biologicals to protect public health. Medication-related errors coupled with unjudicial medication practices often cause a catastrophic impact on the healthcare system globally. The present study aimed to assess the knowledge, attitude, and practice of physicians toward pharmacovigilance and barriers to adverse drug reaction (ADR) reporting at tertiary care hospitals in Khyber-Pakhtunkhwa (KP) province, Pakistan. A descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Our survey revealed that the age, level of education, working experience, and hospital type are related to better HAMs administration scores among physicians. These findings are in line with a recent study reported from KPK Province, Pakistan, where age and working experience of the medical doctors are associated with better drug safety knowledge ( Sharif et al, 2021 ). In our previous study conducted among nurses, no associations though were observed between HAMs administration awareness with age, experience, and level of education ( Salman et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our survey revealed that the age, level of education, working experience, and hospital type are related to better HAMs administration scores among physicians. These findings are in line with a recent study reported from KPK Province, Pakistan, where age and working experience of the medical doctors are associated with better drug safety knowledge ( Sharif et al, 2021 ). In our previous study conducted among nurses, no associations though were observed between HAMs administration awareness with age, experience, and level of education ( Salman et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%